The Implementation of Fingerprint Sensors for Fingerprint Reader Prototypes Using a Microcontroller - Siregar, Victor Marudut Mulia; Siagian, Nancy Florida (Internet of Things and Artificial Intelligence Journal, 2022)
study aims to create a Fingerprint Sensor Implementation System for a Fingerprint Reader Prototype Using a Microcontroller. Implementing the Fingerprint Sensor for the Fingerprint Reader Prototype is run by an application connected by a USB cable. The Fingerprint Sensor Implementation System for the Fingerprint Reader Prototype is made for fast and more accurate attendance and cannot be manipulated. The Fingerprint Sensor Implementation System for the Fingerprint Reader Prototype is the problem. Namely, the attendance problem, which is still manual using books; after that, the design and manufacture of the Fingerprint Reader prototype using a Microcontroller or applications through NetBeans. Then implementation and testing. Then at the trial stage, the Arduino application was carried out. The result of this study is the Fingerprint Sensor Implementation System for the Prototype Fingerprint Reader Using a Microcontroller and development in the Internet of Things.